Literature Study of Legal Protection of Intellectual Property Rights in Creative Industries - Wahyu Suwarni (2021)
Legal protection can be carried out for products of creative industries, including copyrights of books, merchandising, photography, computer programming, music and song, trade secrets, brands and patents. The purpose of this study is to determine the importance of legal protections in the creative industry, through a normative juridical approach with describing the characteristics of legal events. The results of the literature review show that the existence of preventive legal protection (i.e. preventive measures) in the form of registration and repressive (after an intellectual property work violation) takes the form of sanctions. Specific legal protections have been given to the creative industrial products that have been registered through the Directorate General of Intellectual Property with a certificate of Intellectual Property Rights as an evidence to get the protection.